O método dos parâmetros fundamentais em FRX e sua implementação efetiva - Balbino, Daniela Pereira (2014)
The materials characterization techniques, especially the X-ray diffratometry (XRD) and the X-ray fluorescence spectroscopy (XRF) has been well developed since the x-ray discovery at the end of XIX century, the x-ray diffraction phenomena by crystals at the beginning of XX century. Despite the two techniques derived from a common scenario, the quantitative X-ray fluorescence spectroscopy has been an advance more slowly, when compared to X-ray diffractometry. This lead the XRF to bee more knowledge by quick and fast qualitative analyses. By other side XRD technique has the quantitative principles established since the 50 decade of the last century. Around the 80 decade a increase of the interest about the quantitative procedures was did due to the possibility of the numerical treatment of the Sherman equations. This lead to a minimize the need of a individual standards in XRF. Many algorithms was described in the scientific literature about the XRF and it was the main interest in these mastering degree development, because in later times was development an first software by the group with goal the understand so well the quantification methodologies involving in chemical analysis by XRF. This work has as the main subject the validation of a new version of the software IILXRF2012, which was subject of a later mastering in the research group.